Investing in agricultural water management to benefit smallholder farmers in West Bengal, India. - Evans, Alexandra E.V.; Giordano, Meredith A.; Clayton, Terry (International Water Management Institute, 2012)
This Working Paper summarizes research conducted as part of the AgWater Solutions Project in West Bengal between 2009 and 2012. Researchers from the AgWater Solutions Project conducted studies on rainwater harvesting with small ponds (known locally as hapas), improving Access to groundwater through rural electrification and diesel subsidies, and the adoption dynamics of agricultural water management technologies. Research methodologies included rapid rural appraisals, interviews, survey questionnaires and literature reviews. Research suggested that pump rental markets would benefit a large number of poor smallholder farmers. West Bengal has ample groundwater resources, but restrictive policies and high costs make Access difficult. Studies on the adoption dynamics of agricultural water management technologies suggested that adoption of irrigation technology does not necessarily follow a linear path from simple manual methods to ?advanced? motorized technologies, and that cost is not necessarily the main driving factor. Rental markets have emerged as a natural response to demand from those who are unable to own a pump. Wider Access to groundwater through the use of electric and diesel pumps could benefit anywhere from one to four million households. When farmers are able to Access groundwater they cultivate the more high-value boro paddy and diversify their crop mix. Counterproductive policies and rising costs are forcing farmers to cut back on their groundwater use. In areas where groundwater is abundant, easing some of the legal constraints could help to reverse this trend. Rainwater harvesting could benefit from nearly 400,000 to over 600,000 farming households at a 50% adoption rate. The introduction of small rainwater harvesting reservoirs has resulted in benefits, including cultivation of fallow land, higher crop intensity due to cropping in the dry season, new crops, more livestock and aquaculture.